2021
DOI: 10.1002/art.41679
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Binding Protein and CD14, Cofactors of Toll‐like Receptors, Are Essential for Low‐Grade Inflammation–Induced Exacerbation of Cartilage Damage in Mouse Models of Posttraumatic Osteoarthritis

Abstract: Objective. Osteoarthritis (OA) is initiated by pathogenic factors produced by multiple stimuli, including mechanical stress, metabolic stress, and/or inflammaging. This study was undertaken to identify novel low-grade inflammationassociated pathogenic mediators of OA.Methods. Candidate pathogenic molecules were screened using microarray data obtained from chondrocytes exposed to OA-associated catabolic factors. In mice with OA generated by destabilization of the medial meniscus (DMM), low-grade inflammation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 46 publications
(108 reference statements)
1
18
0
Order By: Relevance
“…The top 40 pathways of KEGG results were visualized with a dot plot ( Figure 3(a) ). KEGG results indicated that the PI3K/AKT pathway [ 35 ], Toll-like receptor pathway [ 36 ], NOD-like receptor pathway [ 37 ], TNF pathway [ 38 ], and HIF-1 pathway [ 39 ] were closely related to OA. A network of 6 OA-related pathways and their corresponding targets is shown in Figure 3(b) .…”
Section: Resultsmentioning
confidence: 99%
“…The top 40 pathways of KEGG results were visualized with a dot plot ( Figure 3(a) ). KEGG results indicated that the PI3K/AKT pathway [ 35 ], Toll-like receptor pathway [ 36 ], NOD-like receptor pathway [ 37 ], TNF pathway [ 38 ], and HIF-1 pathway [ 39 ] were closely related to OA. A network of 6 OA-related pathways and their corresponding targets is shown in Figure 3(b) .…”
Section: Resultsmentioning
confidence: 99%
“…The final analysis included 12 studies, 6 of which were animal studies ( 24 29 ) and 6 were clinical studies ( 5 , 30 34 ). Regarding clinical trials, 4 were non-randomized observational studies ( 5 , 30 , 33 , 34 ) and 2 were randomized clinical trials ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…A large body of studies has demonstrated a significant link between a mild proinflammatory state and many diseases. IGL contributes to the development of many diseases, such as metabolic syndrome (MetS), nonalcoholic fatty liver disease (NAFLD), type 2 diabetes mellitus (T2DM) and osteoarthritis [ 55 , 56 , 57 , 58 ]. Meanwhile, studies have shown that these diseases are accompanied by gut microbiota disorder [ 59 , 60 , 61 , 62 ].…”
Section: The Mechanism Of Sara-mediated Igl and Related Inflammatory ...mentioning
confidence: 99%